IMPLEMENTATION OF THE SOCIAL INQUIRY LEARNING MODEL IN SHAPING STUDENTS’ ISLAMIC CHARACTER TO SUPPORT SDG 4 IN THE IBADAH, AKHLAK, AND MU’AMALAH COURSE - Churrahman, Taufik (Antis-publisher, 2025)
Objective: This study aims to evaluate the effectiveness of implementing the Social Inquiry Learning Model in shaping Islamic character among students at UMSIDA, particularly in the Ibadah, Akhlak, and Mu’amalah course. The findings of this research are expected to contribute to the development of learning strategies that are relevant and impactful for Islamic character education at the tertiary level. Method: This study employed a qualitative descriptive approach with an ethnographic research design to explore and evaluate the implementation of the Social Inquiry Learning Model in shaping Islamic character among university students. To achieve a comprehensive analysis, this study integrates two key frameworks: the CIPP evaluation model (Context, Input, Process, Product) and SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). Data were collected through participant observation, in-depth interviews, and document analysis, and were analyzed using the Miles and Huberman model. Results: The test results showed a significant mean difference of -2.302 with a standard deviation of 5.096 and a t-value of -27.112 (df = 35, p = 0.000), indicating a statistically significant improvement in students’ Islamic character after participating in learning activities using the Social Inquiry Model. On average, students' scores increased from 57.72 to 80.75. These activities foster critical thinking, empathy, and social responsibility, all of which are core components of Islamic character. Novelty: This model empowers students to become socially conscious individuals with strong moral integrity, which is essential for Sustainable Development Goal 4 (SDG 4). It also prepares students with 21st-century competencies such as problem-solving, collaboration, and ethical leadership, which are crucial in the contemporary socio-cultural context.